Voter Expectations of Government Formation: The Importance of the Information Context in Coalition Systems: - Mc Elroy, Gail; Bowler, Shaun; Müller, Stefan (My University, 2021)
Can voters in multi-party systems predict which coalition will form the government with any degree of accuracy? To date, studies which explore voter expectations of coalition formation have emphasized individual-level attributes, such as education, but the complexity of the environment at the time the coalitions are forming should also be consequential in enabling (or handicapping) voters in forming expectations. We examine the relative effects of individual level attributes(e.g.education, cognitive mobilization) versus contextual factors (e.g.information availability) in 19 German state elections and 3 German general elections between 2009 and 2017. We find that the ease of identifiability of alternative future governments varies significantly across multi-party systems.We find that respondents are more likely to predict governments that they would like to see in office, that have a higher probability of receiving a majority of seats, and that consist of ideologically proximate parties. Combining survey data with a novel indicator of coalition signals, measured through a quantitative text analysis of newspaper coverage, we also find that voters consider positive pre-election coalition signals when predicting the government. Finally, we find that the information environment is much more relevant for correct coalition predictions than individual-level characteristics of respondents. While individual attributes do influence predictive ability, these factors are strongly dominated by the context in which the prediction is taking place.The information environment has by far the largest effect on predicting coalition outcomes.Our results have implications for the literature on strategic voting in multiparty settings,as well as the literature on accountability.
IN_PRESS
Keywords: German Elections; Coalition politics; Voting behaviour; ELECTIONS; German Politics and Elections; INSTITUTIONS; Political Parties